Extended exergy sustainability analysis comparing environmental impacts of disposal methods for waste plastic roof tiles in Uganda. (2021) - Balcom, Paige; Cabrera, Juliana Mora; Carey, Van P.
Abstract: The world is facing an increasingly dire plastic waste crisis that affects people in developing countries disproportionately more than those in industrialized nations. To compare the environmental effects of end of life disposal and recycling options for plastic/sand roof tiles in Uganda, we use an extended exergy analysis (EEA) to quantify the resources used in the disposal process, the resources saved from replaced virgin materials by recycling, and any additional resources needed to bring the tiles, byproducts, and pollutants to an environmentally acceptable end state. We evaluated disposing of waste plastic/sand roof tiles through open burning, burying, landfilling, pyrolyzing, incinerating in cement kilns, mixing into asphalt to pave roads, and recycling into plastic pavers. With a net exergy avoided of 16, 462 MJ/tonne of tiles, mixing the waste plastic/sand tiles into asphalt roads proved to be the best option followed by pyrolysis with 11, 303 MJ/tonne of net exergy avoided (including remediation). Recycling the tiles into pavers also saved net exergy while burying, landfilling, and incinerating all had negative net exergy values showing that inputting some thermal energy to recycle waste can add value and save net resources. We determined it is not practically feasible to bring all of the pollutants from open burning to an environmentally acceptable end state with the limited technology available in Uganda. However, the method we recommend for remediating CO2 by planting trees requires only 0.7% of the exergy used in CO2 scrubbers currently used in developed countries. Such an empirical study focusing specifically on plastic products and disposal options feasible in developing countries has not been done before, so our paper can be useful to policy makers, multilateral organizations, and NGOs making decisions about solid waste management practices in less-industrialized nations. The results from this paper are valid for HDPE, LDPE, and PP plastics but not for PET or PVC. Highlights: Extended Exergy Analysis (EEA) of plastic waste disposal options in Uganda. Analyzed open burn, pyrolysis, plastic road, new product, bury, incinerate, and landfill options. Proposed CO2 remediation by planting trees requires 0.67% of exergy used in industrial scrubbing. Calculated exergy remediation costs to reach environmentally acceptable end state. Found plastic road, pyrolysis, and recycling into a new product have negative net exergy values.